Solvates of Manganese Trichloride Revisited – Synthesis, Isolation, and Crystal Structure of MnCl3(THF)3. Issue 6 (30th March 2015) - Nachtigall, Olaf; Pataki, Astrid; Molski, Matthias; Lentz, Dieter; Spandl, Johann
Abstract The syntheses and crystal structures of [MnCl3(H2O)(THF)2]·2THF (I), [MnCl4(THF)2][H(THF)2] (II), and [MnCl3(THF)3] (III) are reported. This study shows that former assumptions about the preparation of anhydrous MnCl3 and its etherates, published in the 1960s and earlier, have to be questioned. Instead of the conventional manganese sources, MnF3 was successfully utilized as starting material in THF to give water‐free MnCl3 etherates. These findings are vital for further reactions where reactive but anhydrous MnCl3 derivatives are needed.